Enteric Duplication - Jeziorczak, Paul M.; Warner, Brad W. (Clinics in Colon and Rectal Surgery, 2018)
Enteric duplications have been described throughout the entire gastrointestinal tract. The usual perinatal presentation is an abdominal mass. Duplications associated with the foregut have associated respiratory symptoms, whereas duplications in the midgut and hindgut can present with obstructive symptoms, perforation, nausea, emesis, hemorrhage, or be asymptomatic, and identified as an incidental finding. These are differentiated from other cystic lesions by the presence of a normal gastrointestinal mucosal epithelium. Enteric duplications are located on the mesenteric side of the native structures and are often singular with tubular or cystic characteristics. Management of enteric duplications often requires operative intervention with preservation of the native blood supply and intestine. These procedures are usually very well tolerated with low morbidity.
Keywords: alimentary tract duplication; enteric duplication; heterotopic mucosa; colon; rectum